Activation of natural killer cells by rituximab in granulomatosis with polyangiitis - Urlaub, Doris; Zhao, Shuyang; Blank, Norbert; Bergner, Raoul; Claus, Maren; Tretter, Theresa; Lorenz, Hanns-Martin; Watzl, Carsten; Merkt, Wolfgang (Arthritis Research & Therapy, 2019)
Objective: In the last few years, anti-CD20 antibody rituximab profoundly changed the therapeutic landscape of granulomatosis with polyangiitis (GPA). Here, we investigated whether natural killer (NK) cells may play a role in rituximab’s mechanism of action in GPA. Methods: B cell depletion, NK cell degranulation, and the expression of CD69 and CD16 on NK cells were measured in a series of in vitro experiments using peripheral blood mononuclear cells (PBMCs). In vivo activation of NK cells was investigated in patients receiving rituximab infusions. Cells were analyzed by seven-color flow cytometry. Results: NK cells from GPA patients were activated by immobilized rituximab. Also soluble rituximab activated NK cells, provided that B cells were present. NK cells degranulated and expressed the activation marker CD69 while CD16 expression was decreased. This activation of NK cells by soluble rituximab was accompanied by a reduction of B cells. The next-generation anti-CD20 antibody obinutuzumab showed stronger effects compared to rituximab on both the reduction of B cells and the activation of NK cells. Finally, we found that rituximab led to the activation of NK cells in vivo, provided that B cells were not depleted due to prior rituximab infusions. Conclusion: B cell-bound rituximab activates NK cells in GPA. While NK cells therefore participate in rituximab’s mechanism of action in humans, their potential may be more efficiently exploited, e.g., by Fc engineering of therapeutic antibodies.